Uterine Cells Improved Ovarian Function in a Murine Model of Ovarian Insufficiency. (December 2019) - Reig, Andres; Mamillapalli, Ramanaiah; Coolidge, Alexis; Johnson, Joshua; Taylor, Hugh S.
Primary ovarian insufficiency (POI) is defined as ovarian dysfunction in women younger than 40 years. It affects 1% of the women in this age-group and can occur iatrogenically after chemotherapy. Stem cells have been used in attempt to restore ovarian function in POI. In particular, endometrial mesenchymal stem cells (eMSCs) are easily obtainable in humans and have shown great potential for regenerative medicine. Here, we studied the potential for uterine cell (UC) suspensions containing eMSCs to improve ovarian function in a murine model of chemotherapy-induced POI. Green fluorescent protein (GFP)-labeled UC or phosphate-buffered solution (PBS) was delivered intravenously after chemotherapy. There was a significant increase in oocytes production and serum anti-Müllerian hormone concentrations after 6 weeks, as well as a 19% higher body mass in UC-treated mice. Similarly, we observed an increased number of pups in mice treated with UC than in mice treated with PBS. None of the oocytes or pups incorporated GFP, suggesting that there was no contribution of these stem cells to the oocyte pool. We conclude that treatment with UC indirectly improved ovarian function in mice with chemotherapy-induced POI. Furthermore, our study suggests that endometrial stem cell therapy may be beneficial to young women who undergo ovotoxic chemotherapy.